The Effect of Education through the Whatsapp Application on Increasing Mothers' Knowledge about MP-ASI for Children Aged 6 – 24 Months at the Damai Health Center, West Kutai Regency - Murdiyati; Supriadi B; Rahmawati Wahyuni (Formosa Journal of Science and Technology, 2023)
This study aims to analyze the effect of education via Whatsapp on increasing mothers' knowledge about MP-ASI in children aged 6-24 months at UPT Puskesmas Damai, West Kutai Regency. The design used in this study was a quasy experimental design with a pre-post test with a control group. The population in this study were all mothers with children aged 6-24 months in the working area of ​​the Damai Health Center, West Kutai Regency. The sampling technique used was consecutive sampling. Data analysis technique using paired t-test. The results showed that there was a significant difference in the average knowledge score between the pretest and posttest of the MP-ASI education intervention group via the Whatsapp group with a p-value = 0.000 (<0.05). So it can be concluded that there is an effect of education through WhatsApp on increasing mother's knowledge about MP-ASI in children aged 6-24 months at UPT Puskesmas Damai, West Kutai Regency.